2001
DOI: 10.1016/s0735-1097(00)01186-4
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of regional contractile function after infarction: strain analysis superior to wall thickening analysis in discriminating infarct from remote myocardium

Abstract: Two-dimensional strain analysis is more accurate than planar WT analysis in discriminating dysfunctional from functional myocardium, and it provides a strong correlation between regional myocardial and global ventricular function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
97
0
5

Year Published

2002
2002
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(114 citation statements)
references
References 36 publications
12
97
0
5
Order By: Relevance
“…2 and 4. This finding is consistent with a previous report, which showed circumferential strain to be more sensitive to the presence of myocardial infarction than wall thickening (8).…”
Section: Relationship Between Scar Extent and Circumferential Strainsupporting
confidence: 93%
“…2 and 4. This finding is consistent with a previous report, which showed circumferential strain to be more sensitive to the presence of myocardial infarction than wall thickening (8).…”
Section: Relationship Between Scar Extent and Circumferential Strainsupporting
confidence: 93%
“…Resting LV dysfunction can be precisely assessed by use of cine acquisitions with tissue tagging and strain analysis (52). As with echocardiography, the assessment of LV enddiastolic wall thickness is useful for ruling out viability.…”
Section: Mrimentioning
confidence: 99%
“…20 Quantitative assessment of contractile function by magnetic resonance (MR) tissue tagging and strain analysis suggested that strain could accurately detect dysfunctional myocardium, with a cutoff value of -20%. 21 Reisner et al developed and validated the AFI algorithm to assess global LV function, and demonstrated a strong linear correlation between WMSI and GLS with R 2 = 0.55. 12 Our results show good agreement with theirs.…”
Section: Comparison Of Gls With Results Obtained Using Other Methodsmentioning
confidence: 99%